Methods for determining the position of the curve in the plan and the influence of the geometry of the track on the indicators of interaction between the track and the rolling stock - E. A. Sidorova; O. N. Vaganova; A. Yu. Slastenin (Вестник Научно-исследовательского института железнодорожного транспорта)
The article substantiates the necessity of supplementing the existing estimate of the track position in the plan by the difference of adjacent bending arrows with an estimate of deviations from the fixed initial position, which ensures the constancy of the characteristics of a single-radius curve or the components of a multi-radius curve along their entire length. As a fixed initial position of the reference base (base position), it is proposed to accept the design position or the position of the track after the repair performed according to the project, and in the absence of the project, the calculated position obtained using verified programs. The question of determining the values of the deviation of the position of the curves at individual points from the base position and their ranking for different variants of recording the curves is considered. As possible options for surveying are considered Geodetic measurement methods using Cartesian and polar coordinate systems, methods of obtaining information from transformed data from sensors of track measuring cars, as well as the classical method of measuring the arrows of the bend of a curve.The article presents the results of calculating the indicators of the interaction between the track and the rolling stock (frame and horizontal transverse forces, lateral deflections of rails) when modeling the motion of a freight car along curves, the parameters of which were obtained on the basis of analysis of data from experimental sections. The calculation results are correlated with the analyzed data on the presence of deviations from the base position in the curves.